The lygaeoid bug genus Sadoletus Distant (Hemiptera: Heteroptera: Heterogastridae) from Japan - Ban, Teruaki; Ishikawa, Tadashi (Zootaxa, 2013)
The Japanese species of the heterogastrid genus Sadoletus Distant are revised taxonomically. Three species are recog-nized, including a new species, S. ryukyuensis sp. nov., which has been regarded so far as S. valdezi Bergroth in Japan. "True" S. valdezi is confirmed in Japan as well. A key to the Japanese species is provided.